ANALISIS PERILAKU PENGGUNA PADA BANGUNAN KANTOR DESA: SEBUAH KAJIAN ARSITEKTUR PERILAKU - Nugraha, I.G.C.A.; Ulag, A.A.T.; Girindra, E.R.; Hastagina, M.H.A.; Prajnawrdhi, T.A. (Buletin Udayana Mengabdi, 2024)
Behavioral architecture in the Sangsit village office building is a design approach that considers psychological factors and human behavior in creating an environment that facilitates social interaction, productivity and comfort in the workplace. This article aims to provide an overview of the concepts and principles of architectural behavior that can be applied in designing Sangsit village office buildings that offer welfare and work effectiveness. This article finds that architectural behavior applied to room settings is able to influence and express how the shape of a room is towards the state of the community. Keywords : Behavioral Architecture, Village Office, Factors